2006
DOI: 10.1038/sj.leu.2404162
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised proteome analysis of human leukaemia cells identifies the Valosin-containing protein as a putative marker for glucocorticoid resistance

Abstract: The response to initial glucocorticoid therapy in childhood acute lymphoblastic leukaemia (ALL) reliably predicts the response to multiagent chemotherapy. Patients resistant to glucocorticoids (prednisone poor responders (PPR)) have a poorer event-free survival compared to glucocorticoid-sensitive patients (prednisone good responders (PGR)). A casecontrol study was performed to investigate differential protein expression in leukaemic blasts from PGR and PPR childhood ALL patients. Two-dimensional gel electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…[68][69][70][71][72][73][74][75][76][77][78] While in the era of genomics the number of papers in the field of leukemia has risen amazingly, it remains difficult to filter out the information, which can be used for improved treatment quality and better prevention of disease recurrence. Certainly one prerequisite is reproducibility of data, and thus, uniform approaches are needed if such techniques shall be used routinely in clinical diagnostics and for risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70][71][72][73][74][75][76][77][78] While in the era of genomics the number of papers in the field of leukemia has risen amazingly, it remains difficult to filter out the information, which can be used for improved treatment quality and better prevention of disease recurrence. Certainly one prerequisite is reproducibility of data, and thus, uniform approaches are needed if such techniques shall be used routinely in clinical diagnostics and for risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…VCP has a pro-survival function, demonstrated both in yeast and in mammalian cells [46,47]. Elevated VCP levels were found to correlate with increased incidence of metastasis in prostate cancer, esophageal carcinoma, and leukemia [48,49]. In several cell types expression of mutant VCP or downregulation of VCP led to apoptosis [47].…”
Section: The Proapoptotic Role Of Sapmentioning
confidence: 97%
“…The expression of VCP has been found to be related to the pathological state and clinical outcome of human tumors such as childhood acute lymphoblastic leukemia [25] . The results from our study indicated that the C allele of VCP rs2074549 was significantly associated with the risk of occurrence of grade 3+ myelosuppression directly after CRT in NPC patients (P=0.008), particularly in the subgroup of patients at stage T3 and T4 (P=0.003).…”
Section: Discussionmentioning
confidence: 99%